Child neurodevelopment and mental health after surgical ventricular septal defect repair: risk and protective factors. (27th August 2018) - Eichler, Anna; Köhler‐Jonas, Nicola; Stonawski, Valeska; Purbojo, Ariawan; Moll, Gunther H; Heinrich, Hartmut; Cesnjevar, Robert A; Kratz, Oliver
Abstract : Aim: This case–control study examined the long‐term consequences of surgical correction for ventricular septal defect (VSD; the most common congenital heart defect) in infancy. It assessed children who had undergone VSD surgery and the factors related to maternal conditions, surgery, and hospital stay. Method: Thirty‐nine children (23 females, 16 males; age range 6y 1mo–9y 7mo [mean 7y 4mo, SD 1y]) with repaired isolated, non‐syndromic, non‐genetic VSD were compared with 39 typically developing children (22 females, 17 males; age range 6y–9y 2mo [mean 7y 3mo, SD 10mo]). The children completed behavioural tests of neurodevelopment and a quality of life (QoL) questionnaire. Mothers rated children's emotional/behavioural symptoms and QoL. Measures of maternal parenting behaviour and psychopathology were treated as moderators. Results: Affected children showed reduced language skills ( p =0.002) unless mothers reported high parenting behaviour subscale scores ( p =0.04). Children's anxiety symptoms were elevated when mothers had anxiety symptoms ( p =0.01). Longer hospital stay was associated with lower intelligence ( p= 0.003) and psychomotor scores ( p =0.006). Longer scars predicted elevated child anxiety ( p =0.008), and age at surgery and QoL were inversely related ( p =0.01). Interpretation: Impairments could be mitigated if VSD repair was performed early in life with a relatively small scar and uncomplicated hospital stay. This outcome depends on maternal parenting behaviour and anxiety symptoms. What this paper adds: Children's cognitive and psychomotor development after surgical ventricular septal defect repair was unimpaired. Children showed no mental health restrictions when their mothers reported few anxiety symptoms themselves. Language impairments might be preventable by pro‐active parenting. The outcome also depends on variables related to surgery and hospital stay. What this paper adds: Children's cognitive and psychomotor development after surgical ventricular septal defect repair was unimpaired. Children showed no mental health restrictions when their mothers reported few anxiety symptoms themselves. Language impairments might be preventable by pro‐active parenting. The outcome also depends on variables related to surgery and hospital stay. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.